Analysis of some conserved miRNAs in hazelnut (Corylus avellena L. and Corylus colurna L.) by real-time PCR - Yirmibes, Busra; Aydin, Hatice Nur; Omeroglu Ulu, Zehra; Ulu, Salih; Ozdemir Ozgenturk, Nehir (YILDIZ TECHNICAL UNIV, 2021)
Hazelnut is an important plant species which is used in food industry, dye industry, wood-chopping and stock firming and it has also benefits for health due to nutrient component. Economically valuable Corylus avellena and Corylus colurna used as rootstock are the most common cultivars. Although many studies have been made about micro RNA in plants so far, there are few studies in hazelnut. miRNAs are 18-25 nucleotide, short and single strand non-coding RNAs. miRNAs called as post-transcriptional gene regulators cause repress or cleavage of their target mRNA. In particularly in plants, they cause cleavage of mRNA and so play role in developmental process, response process to biotic and abiotic stresses like drought, salt, cold or UV. Conserved miRNAs are miRNAs which have same function in different plant species and are conserved from very old times to the present. In this study, we aimed that analyzing of some conserved miRNAs (miR159, miR160, miR171, miR396, miR2919 and miR8123) in hazelnut (Corylus avellena L. and Corylus colurna L.) by Real-Time PCR. We found which these conserved miRNAs are present in both hazelnut species.
Keywords: Conserved microRNA; hazelnut; Corylus avellena L.; Corylus colurna L.; real-time PCR; cDNA; PLANT MICRORNAS; EVOLUTION; IDENTIFICATION; SEQUENCES; Engineering